2022
DOI: 10.48550/arxiv.2208.03920
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Weinberg operator contribution to the CP-odd nuclear force in the quark model

Abstract: The contribution of the CP violating three-gluon interaction, proposed by Weinberg, to the shortrange CP-odd nuclear force is evaluated in the nonrelativistic quark model. We first show that the naive leading contribution generated by the quark exchange process vanishes at sufficiently short distance within the resonating group method, by considering the one-loop level gluon exchange CP-odd interquark potential induced by the Weinberg operator with massive quarks and gluons. We then estimate the true leading c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 160 publications
0
2
0
Order By: Relevance
“…The Weinberg operator does not violate the chiral symmetry, so it is expected that the neutron EDM and the contact N N interaction are the leading contribution to atomic EDMs, and the CP-odd πN interactions are next-to-leading order (NLO) in the context of the chiral perturbation theory. However, the contribution of the contact N N interaction in light nuclei is not large [13,14] while the pion exchange contribution is enhanced in heavy nuclei, so we consider only the isovector CP-odd πN interaction…”
Section: Chiral Perturbation Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The Weinberg operator does not violate the chiral symmetry, so it is expected that the neutron EDM and the contact N N interaction are the leading contribution to atomic EDMs, and the CP-odd πN interactions are next-to-leading order (NLO) in the context of the chiral perturbation theory. However, the contribution of the contact N N interaction in light nuclei is not large [13,14] while the pion exchange contribution is enhanced in heavy nuclei, so we consider only the isovector CP-odd πN interaction…”
Section: Chiral Perturbation Theorymentioning
confidence: 99%
“…This operator was first calculated in the Higgs doublet model [7], and then, it has been found that some other models also generate it such as the supersymmetric model [8]. While the relation between this operator and the neutron EDM has been investigated widely [9,10,11], its value for the CP-odd nucleon-nucleon (N N ) interaction, which is expected to give the main contribution to the atomic EDMs, has only been evaluated quite recently [12,13].…”
Section: Introductionmentioning
confidence: 99%